DINAMIKA PERADABAN ISLAM MASA BANI UMAYYAH DI TIMUR DAN IMPLIKASINYATERHADAP ILMU PENGETAHUAN - Calista Ramadhani, Auryn; Nurzena, Nurzena (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic civilization during the Umayyad Dynasty experienced significant development through territorial expansion into Eastern regions such as Persia and Central Asia. This expansion influenced not only political aspects but also the social, cultural, and intellectual development of the Islamic world. This study aims to analyze the dynamics of Islamic civilization during the Umayyad era in the Eastern territories and its implications for the advancement of knowledge. The findings reveal that cultural interaction between Arab society and local communities encouraged acculturation and knowledge transfer that enriched Islamic intellectual traditions. In addition, the Arabization policy strengthened the role of Arabic as the language of administration and science. These developments later became the foundation for the advancement of Islamic knowledge in subsequent periods